TRAINING ON MEASURING THE FINANCIAL FEASIBILITY OF THE BUSINESS AT MSME RAJUT DENZAA IN LAMPUNG - Yusbardini, Yusbardini (Transpublika Publisher, 2024)
Feasibility analysis is essential for every MSME (Micro, Small, and Medium Enterprises) as a consideration for whether a business is feasible to continue. The result of financial feasibility analysis is expected to determine whether the business plan is economically profitable or not. The purpose of this service is to provide training on measuring business feasibility at MSME Rajut Denzaa in Jambi. This training aims to help MSME Rajut Denzaa understand whether the business they are running is financially viable. Viable means that the income received from the business exceeds all the costs incurred during its operation. The owner of the MSME must truly understand whether their business is indeed feasible to continue. Lack of knowledge on financial feasibility measurement is the core problem of MSME Rajut Denzaa. Therefore, the PKM Team needs to provide this training to help MSME Rajut Denzaa understand whether their business is feasible to continue or not.